Seni Beluk sebagai Identitas Budaya di Kampung Adat Cikondang - Adilaturohman, Nadila; Fauziyah, Nurul Zahra; Nuranggraeni, Klara; Hanif, Hilman; Yanti, Devi; Suris, Rezika; Supriatna, Mamat (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
This study aims to explore the role and function of Seni Beluk as a cultural identity of the indigenous community in Kampung Adat Cikondang, Bandung Regency. Seni Beluk is a traditional Sundanese vocal art passed down through generations, rich in spiritual and social values. The research employed a qualitative case study approach involving field observation, in-depth interviews, and documentation. The results show that Seni Beluk functions not only as entertainment but also as a medium for religious preaching, moral advice, and reinforcement of customary values in communal life. The lyrics are recited during significant events such as childbirth, thanksgiving, house construction, and circumcision ceremonies, carrying deep religious and social meanings. The main challenge in its preservation lies in the lack of generational continuity due to the younger generation’s limited interest and vocal skills. Preservation efforts are carried out through cultural education and documentation. Seni Beluk stands as a symbol of cultural resilience for the Cikondang community, and its integration into counseling services highlights its potential in developing students' character. Therefore, preserving Seni Beluk is crucial to maintaining local cultural identity in the face of modernization.